Bridging traditional Chinese medicine and Alzheimer’s disease: the pivotal role of gut microbiota in multitarget therapeutic mechanisms - Wu, Weidong; Meng, Tianwei; Han, Lichao; Jin, Fangfang; Han, Pengfei; Zhou, Yanyan (Frontiers in Pharmacology, 2025)
Microbiota-gut-brain axis communication represents another crucial pathway in the pathogenesis of Alzheimer’s disease (AD), whereby gut microbiota significantly impacts AD pathology by modulating immune, metabolic, digestive, and neurological functions. Although research on treating AD through gut microbiota interventions is advancing, substantial breakthroughs remain limited. Given AD’s complex pathological mechanisms, Traditional Chinese Medicine (TCM) presents a clear advantage with its multi-target effects. During the processes of TCM intake, absorption, and therapeutic action, the gut microbiota serves both as a mediator and as a therapeutic target. However, the mechanisms by which TCM interacts with gut microbiota to exert beneficial effects on AD remain largely unclarified. Here, we review the mechanisms through which TCM may intervene in AD from the perspective of gut microbiota, examining the potential mechanisms and clinical application prospects of Chinese herbal medicine in regulating the gut microbiome. This provides a novel theoretical foundation and methodological support for further research into herbal therapies for AD.